Hyper-personalization in Social Media Marketing (Conceptual Framework) - Nurhayati, Lina; Widodo, Arry; Silvianita, Anita; Rubiyanti, Nurafni (International Journal of Integrative Sciences, 2024)
This study aims to analyze the relationship between social media marketing, attitude, subjective norm, perceived ease of use, perceived usefulness, behavior intention, and purchase behavior using a correlational approach. The sample population consists of Tiktok and Shoppe application users selected by purposive sampling method. The sample consists of generation Z who have seen live Shoppe and Tiktok, with domicile in Bandung. The Partial Least Squares (PLS) approach to Structural Equation Modeling (SEM) is used to analyze the collected data. The results showed that social media marketing has a significant positive influence on attitude, subjective norm, perceived ease of use, and perceived usefulness. Attitude, subjective norm, perceived ease of use, and perceived usefulness also have a significant positive influence on behavior intention. In the end, behavior intention has a significant positive influence on purchase behavior. In conclusion, social media marketing plays an important role in shaping attitudes, subjective norms, perceived ease of use, and perceived usefulness that will affect behavior intention and purchase behavior. Companies must take advantage of features available on social media, such as live Shoppe and Tiktok, and provide relevant and interesting content for consumers. In addition, companies must also pay attention to consumer preferences and needs in promoting products or services promoted through social media